2013
DOI: 10.1080/00405000.2013.767430
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid mixed media nonwovens composed of macrofibers and microfibers. Part I: three-layer segmented pie configuration

Abstract: Nonwoven fabrics, composed of microdenier fibers, can be easily created by using splittable bicomponents such as segmented pie. Hydroentangling has been shown as a very effective method for mechanically splitting these fibers. Such structures are known to form a densely packed nonwoven fabric with concomitant consequences in low porosity and tear strength. It is not, therefore, uncommon to insert a reinforcing scrim as a "rip-stop" mechanism in the middle of such structures to improve their properties, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…They concluded that the cube root averaged diameter concept of Tafreshi et al (2009) could be used to design a bimodal fi lter media quite successfully. Jaganathan et al (2008) studied the pressure drop across bi-component fi lter media composed of fi bres showing bimodal diameter distributions. They observed that the area-weighted average of the fi bre diameters in a bimodal fi lter, as proposed by Brown and Thorpe (2001), resulted in a relatively good estimation of an equivalent unimodal fi bre diameter.…”
Section: Particle Fi Ltration Behaviour Of Composite Nonwovensmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the cube root averaged diameter concept of Tafreshi et al (2009) could be used to design a bimodal fi lter media quite successfully. Jaganathan et al (2008) studied the pressure drop across bi-component fi lter media composed of fi bres showing bimodal diameter distributions. They observed that the area-weighted average of the fi bre diameters in a bimodal fi lter, as proposed by Brown and Thorpe (2001), resulted in a relatively good estimation of an equivalent unimodal fi bre diameter.…”
Section: Particle Fi Ltration Behaviour Of Composite Nonwovensmentioning
confidence: 99%
“…This model was claimed to have good predictive capability. Hollowell et al (2013) investigated the air permeability characteristics of hybrid mixed media nonwovens composed of macro-and micro-fi bres. They developed a series of hybrid mixed media nonwovens by hydroentangling a homo-component spunbond fabric sandwiched between two layers of 16-segmented pie bi-component spunbond fabric.…”
Section: [42]mentioning
confidence: 99%
“…Hollowell et al. [14] combined the biocomponent hollow segmented pie microfiber with homocomponent fiber to form a three-layer structure, which improved the permeability, mechanical properties and porosity of the nonwoven fabric. Zhao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports on bicomponent materials were focused on the methods of fibrillation and the mechanical properties [12]. Hollowell et al [13] used hollow pie wedge bicomponent to produce nonwoven fabrics with low porosity and tear strength by hydroentangling. Lu and Qian [14,15] recently investigated the splitting method of bicomponent spunbond fiber and found the hydroentangling was the best.…”
Section: Introductionmentioning
confidence: 99%